Optoelectronic Performance Analysis of Low-Energy Proton Irradiation and Post-Thermal Annealing Effects on InGaAs Solar Cell - Zhuang, Y.; Aierken, A.; Lei, Q. Q.; Fang, L.; Shen, X. B.; Heini, M.; Guo, Q.; Guo, J.; Yang, X.; Mo, J. H.; Fan, R. K.; Li, J.; et al. (Frontiers in Physics, 2020)
The electrical and spectral properties of 150 KeV proton-irradiated MBE-grown In0.53Ga0.47As single junction solar cell and its post-thermal annealing properties were investigated. Both simulation and experimental methods were applied to analyze the irradiation-induced displacement damage and degradation mechanism of cell performance. The results show that most protons would penetrate through the In0.53Ga0.47As emitter and stop in the base region, causing differing extents of electric and spectral degredation. When proton fluence were 1 × 1012 and 5 × 1012 p/cm2, the remaining factor of Isc, Voc, Pmax, and FF were degraded to 0.790, 0.767, 0.558, 0.921 and 0.697, 0.500, 0.285, 0.817, respectively. Severer degradation was found in short wave lengths compared to long wave lengths of the solar cell spectral response. After annealing treatments, the normalized Isc, Voc, Pmax, and FF, significantly recovered from 0.697, 0.500, 0.285, and 0.817 to 0.782, 0.700, 0.499, and 0.912 (fluence: 5 × 1012 p/cm2), and the irradiation-induced defects in the whole emission area and part of the base area were annihilated, so the observed recovery of the short wavelength of the solar cell was greater than the long wavelength. The performance analysis in this work provided valuable ways to improve the photoelectric efficiency of space solar cells.